Analisis pemecahan masalah pada soal cerita matematika materi pengukuran kelas IV SDN Jembangan 1 tahun ajaran 2022/2023 - Isnaini Putri; Sri Handayani (UNIVERSITAS SLAMET RIYADI, 2024)
The purpose of this study was to analyze problem solving in mathematics word problems on pengukuran material and to describe what factors influence problem solving in mathematics word problems on pengukuran material for high, medium, and low category students in Class IV of SDN Jembangan 1 in the 2022/2023 academic year. The research was conducted at SDN Jembangan 1 in the 2022/2023 academic year with descriptive qualitative research. Data collection methods are observation, interview, and documentation techniques. The research subjects were fourth grade students. Using triangulation techniques. Learners with high categories are able to understand the problem, make plans and carry out plans. Learners are able to look back at answers. Learners with moderate categories are able to complete the story problem test with problem solving indicators well but in changing the unit is still wrong so that the final answer is not correct. Learners with low ability have not been able to find the right way to solve problems so that they make the answer incorrect. Keywords: Problem Solving, Mathematics Story Problems, pengukuran Material.